Nexus Network Journal Architecture, Mathematics and Structure - Williams, Kim.; SpringerLink (Online service) (Basel : Birkhäuser Basel, 2009)
The title of this issue of the Nexus Network Journal, "Architecture, Mathematics and Structure," is deliberately ambiguous. At first glance, it might seem to indicate the relationship between what buildings look like and how they stand up. This is indeed one aspect of what we are concerned with here. But on a deeper level, the fundamental concept of structure is what connects architecture to mathematics. Both architecture and mathematics are highly structured formal systems expressed through a symbolic language. For architecture, the generating structure might be geometrical, musical, modular, or fractal. Once we understand the nature of the structure underlying the design, we are able to "read" the meaning inherent in the architectural forms. The papers in this issue all explore themes of structure in different ways.
Letter from the Editor -- Letter from the Editor -- Research -- Continuity versus Discretization -- Cognitive-Mathematical Approaches for Evaluating Architectural Contextual Fit -- Nicola Zabaglia and the School of Practical Mechanics of the Fabbrica of St. Peter s in Rome -- Mathematics for/from Society: The Role of the Module in Modernizing Japanese Architectural Production -- Can Chaos Theory Explain Complexity In Urban Fabric? Applications in Traditional Muslim Settlements -- Antonelli s Dome for San Gaudenzio: Geometry and Statics -- Music and Architecture: A Cross between Inspiration and Method -- Using Key Diagrams to Design and Construct Roman Geometric Mosaics? -- The N4C Joint -- Didactics -- Geometries of Imaginary Space: Architectural Developments of the Ideas of M. C. Escher and Buckminster Fuller -- Mathematical Machines: A Laboratory for Mathematics -- Conference Report -- Fortification in Focus Mathematical Methods in Military Architecture of the 16th and 17th Centuries and their Sublimation in Civil Architecture.
Keywords: Mathematics; Architecture; Mathematics; Mathematics, general; Architectural History and Theory; Electronic books